2017
DOI: 10.1111/1751-7915.12870
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the impact of microbial community biodiversity on pharmaceutical biotransformation during wastewater treatment

Abstract: SummaryIn addition to removing organics and other nutrients, the microorganisms in wastewater treatment plants (WWTPs) biotransform many pharmaceuticals present in wastewater. The objective of this study was to examine the relationship between pharmaceutical biotransformation and biodiversity in WWTP bioreactor microbial communities and identify taxa and functional genes that were strongly associated with biotransformation. Dilution‐to‐extinction of an activated sludge microbial community was performed to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 44 publications
(44 reference statements)
5
36
0
Order By: Relevance
“…While positive associations between biological richness and the rates of particular metabolic processes have been observed (Bell et al ., ; Cardinale, ; Gravel et al ., ; Peter et al ., ; Bouvier et al ., ; Cardinale et al ., ; Dell'Anno et al ., ; Hernandez‐Raquet et al ., ; Philippot et al ., ; Johnson et al ., ; Evans et al ., ; Stadler et al ., ), it remains unclear whether these positive associations are a general feature of the metabolic processes performed by microbial communities. For example, while many studies have observed positive associations between biological richness and the rates of some metabolic processes (Bell et al ., ; Cardinale, ; Gravel et al ., ; Peter et al ., ; Bouvier et al ., ; Cardinale et al ., ; Dell'Anno et al ., ; Hernandez‐Raquet et al ., ; Philippot et al ., ; Johnson et al ., ; Evans et al ., ; Stadler et al ., ), other studies have not (Salonius, ; Griffiths et al ., ; Wertz et al ., ; Szabó et al ., ; Peter et al ., ; Pholchan et al ., ; Graham et al ., ; Roger et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While positive associations between biological richness and the rates of particular metabolic processes have been observed (Bell et al ., ; Cardinale, ; Gravel et al ., ; Peter et al ., ; Bouvier et al ., ; Cardinale et al ., ; Dell'Anno et al ., ; Hernandez‐Raquet et al ., ; Philippot et al ., ; Johnson et al ., ; Evans et al ., ; Stadler et al ., ), it remains unclear whether these positive associations are a general feature of the metabolic processes performed by microbial communities. For example, while many studies have observed positive associations between biological richness and the rates of some metabolic processes (Bell et al ., ; Cardinale, ; Gravel et al ., ; Peter et al ., ; Bouvier et al ., ; Cardinale et al ., ; Dell'Anno et al ., ; Hernandez‐Raquet et al ., ; Philippot et al ., ; Johnson et al ., ; Evans et al ., ; Stadler et al ., ), other studies have not (Salonius, ; Griffiths et al ., ; Wertz et al ., ; Szabó et al ., ; Peter et al ., ; Pholchan et al ., ; Graham et al ., ; Roger et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Biological richness (e.g. the number of functionally different genotypes within a community) is one factor that may be important (Bell et al, 2005;Duffy, 2009;Cardinale, 2011;Gravel et al, 2011;Peter et al, 2011;Bouvier et al, 2012;Cardinale et al, 2012;Dell'Anno et al, 2012;Hernandez-Raquet et al, 2013;Philippot et al, 2013;Johnson et al, 2015a;Evans et al, 2017;Stadler et al, 2017). Communities with higher biological richness are more likely to contain genotypes that have direct or indirect positive effects on the rate of a particular metabolic process (Loreau et al, 2001;Balvanera et al, 2006;Cardinale et al, 2006;Cardinale, 2011;Cardinale et al, 2012;Tilman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The changes in operating conditions are considerably related to microbial population dynamics in biological treatment processes. The shifts of microbial communities strongly impact on the removal of pharmaceuticals, as reported by recent studies [56,57]. This may be one of the reasons why the order of SREs was different in individual treatment processes.…”
Section: Removal Of Pharmaceuticals By Biological Treatment Processesmentioning
confidence: 86%
“…The degree of microbial diversity and pharmaceutical removal are influenced by operational parameters, such as SRT, redox condition, and carbon supply [57,59]. Stadler et al (2018) conducted batch experiments for the pharmaceutical biotransformation and observed that metabolic genes, such as dehydrogenases, amidases, and monooxygenases, were positively associated with the extent of pharmaceutical biotransformation [56]. In order to better understand the removal characteristics of pharmaceuticals in biological treatment processes, future work should consider the effects of operating conditions on variations in microbial communities and possible relations between these microbial communities and the removal of pharmaceuticals.…”
Section: Removal Of Pharmaceuticals By Biological Treatment Processesmentioning
confidence: 99%
“…There is no data on either the removal efficiency or the concentration of antimicrobials in Polish WWTPs. The concentration of PhACs in the environment depends on the consumption of pharmaceuticals, which is country-and culture-specific, and their pharmacokinetics, and may considerably vary with seasons and physicochemical properties of these compounds, various process operating parameters of WWTPs, and bacterial community structure [9,10]. According to the European Centre for Disease Prevention, in 2018 the corresponding population-weighted mean consumption of antimicrobials (in defined daily dose (DDD) units per 1000 inhabitants per day) in European Union and European Economic Area countries was 18.4 DDD.…”
Section: Introductionmentioning
confidence: 99%